Flexural behaviour of concrete‐filled steel hollow sections beams - Soundararajan, Arivalagan; Shanmugasundaram, Kandasamy (Journal of Civil Engineering and Management, 2008)
This paper presents an experimental study of normal mix, fly ash, quarry waste and low strength concrete (brick‐bat lime concrete) contribution to the ultimate moment capacity of square steel hollow sections. Fifteen simply supported beam specimens of 1200‐mm long steel hollow sections filled with normal mix, fly ash, quarry waste and low‐strength concrete and identical dimensions of hollow sections were experimented. Extensive measurements of such material properties, strain and deflection were carried out. Theoretical studies of ultimate moment capacity of a beam specimen were also calculated in this study for comparison's sake. These experimental investigation results showed that normal mix, fly ash, quarry waste and low‐strength concrete enhance the moment carrying capacity of steel hollow sections. Furthermore, in these studies it can be found that normal mix, fly ash and quarry waste concrete can be used in composite construction to increase the flexural capacity of steel hollow sections.Betonšerdžių plieninių stačiakampio skerspjūvio vamzdinių sijų elgsenaSantrauka. Pateikiamas normalaus, lakiųjų pelenų, akmenų skaldymo atliekų ir mažo stiprumo (skaldytųjų plytų kalkinio) betonų įtakos kvadratinio skerspjūvio plieninių vamzdžių ribinei lenkiamajai galiai eksperimentinis tyrimas. Išbandyta penkiolika dviatramių sijų bandinių iš 1200 mm ilgio plieninių tuščiavidurių profiliuočių, pripildytų normalaus, lakiųjų pelenų, akmenų skaldymo atliekų ir mažo stiprumo betonų ir identiškų matmenų tuščiavidurių profiliuočių. Atlikti didelės apimties medžiagų savybių, santykinių deformacijų ir įlinkių matavimai. Lyginant teoriškai apskaičiuota sijų laikomoji galia. Eksperimentinio tyrimo rezultatai parodė, kad normalus, lakiųjų pelenų, akmenų skaldymo atliekų ir mažo stiprumo betonai didina plieninių tuščiavidurių profiliuočių lenkiamąją galią. Be to, iš šio tyrimo galima matyti, kad normalus, lakiųjų pelenų ir akmenų skaldymo atliekų betonus galima naudoti kompozitinių konstrukcijų plieninių tuščiavidurių profiliuočių lenkiamajai galiai didinti.Reikšminiai žodžiai: betonšerdės sijos, dvitaškė apkrova, analitinis modelis, ribinė lenkiamoji galia.First Published Online: 14 Oct 2010